The linguistic representation of abstract concepts in learning science: a cognitive discursive approach - Zacharias, Sally (2018)
Learning scientific concepts can be challenging for many pupils and consequently much research has been carried out to locate and explain the social and cognitive processes involved in bringing about changes to learners’ abstract conceptual understandings. This thesis contributes to this field by offering a text-world account (Werth 1999, Gavins 2007a) of how scientific concepts are constructed and linguistically represented in classroom discourse. More specifically, its first aim is to explore how a group of twenty, first year secondary pupils and their teacher construct and linguistically represent the abstract scientific concept of heat energy (and related concepts) in discourse. In so doing, it examines how the concept emerges and develops during a series of classroom activities, including a teacher-led demonstration, a simulated role-play and a group discussion/writing task, in addition to teacher and pupil interviews. By using the Text World Theory framework (see Gavins 2007a; Werth 1999) to focus on the linguistic choices and their corresponding cognitive effects, it becomes possible to explore the cognitive architecture of the pupils during the learning events and interviews. Thus, it is hoped that this study makes an innovative contribution to the field of cognitive linguistics and science education by explaining and exemplifying how learners’ scientific concepts develop in naturalistic settings (Amin 2015). As a text-world approach to investigating classroom discourse is a relatively new area of exploration, the thesis also aims to examine the effectiveness of the text-world framework to explore multimodal, interactive classroom environments. The class involved in this study belonged to a state secondary school in a large urban city in Scotland. There was a broad ability range amongst its pupils, many of whom spoke languages other than English at home. The data generated was the result of a four-month prolonged investigation with the class, which resulted in the video and audio recordings of 15 lessons, 8 pupil interviews and 5 teacher interviews. Part of this data was later transcribed and analysed using the text-world framework. This framework proves to be well-suited to the task of investigating the conceptual structure of the classroom participants, due to its ability to track and explore multiple conceptual worlds established through spatial and temporal shifts, as well as modality and metaphor. By applying the framework to the relatively unexplored context of the classroom, extensions to the framework are made that show how the classroom discourse, the knowledge frames of the pupils as well as the social and concrete world of the classroom, play a key role in the development of abstract thought in a classroom setting.